Draft Annual Plan 2004-05 Government of Goa - Planning Commission (Planning Commission, 2004)
Goa is the only State in the country which possesses the distinction of achieving high level of both economic and social development. An average GSDP growth of over 10% per annum, the highest per capita income and high level of human development indicators vouch for the heights of development achieved by the State. Many comparative studies carried out by reputed agencies/economists have acknowledged this fact.
Government of Goa, Directorate of Planning, Statistics and Evaluation